Fecaloma impaction and stercoral ulcer. Issue 3 (6th February 2020) - Huang, Wei‐Chen; Huang, Tien‐Yu; Chen, Peng‐Jen; Shih, Yu‐Lueng; Chang, Wei‐Kuo; Hsieh, Tsai‐Yuan; Huang, Hsin‐Hung
Abstract: A 76‐year‐old female with a history of chronic constipation presented with progressive abdominal pain and blood‐tinged stools at the emergency room. Upon examination, the computed tomography scan revealed bowel obstruction by a huge fecaloma impaction (9 × 7 cm) with focal thickening of the colonic wall and mural enhancement over the rectum. After gently evacuating feces manually followed by enema, subsequent colonoscopy also confirmed a large stercoral ulcer (6 × 5 cm) over the rectum with diffusely edematous and friable, sloughing mucosa. With conservative treatment, her symptoms were relieved uneventfully. Her condition improved and she was discharged after receiving education about constipation management. Constipation in the elderly population is common. However, in this instance, if left untreated, massive ulcer bleeding or perforation could occur. Therefore, such cases should be evaluated with more caution in order to prevent the development of irreversible complications.